2018
DOI: 10.1111/eci.12907
|View full text |Cite
|
Sign up to set email alerts
|

Kidney function monitoring and nonvitamin K oral anticoagulant dosage in atrial fibrillation

Abstract: Noncompliance with kidney function monitoring recommendations is common in NVAF patients starting NOAC, especially in elderly patients with kidney dysfunction. Compliance with kidney function monitoring recommendations was associated with adequate NOAC dosage at 1-year follow-up. Further studies are warranted to evaluate the implication of kidney function monitoring on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…(C) Real‐world studies results concerning dose adjustments of apixaban. (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(C) Real‐world studies results concerning dose adjustments of apixaban. (D) Results from direct oral anticoagulants overall adjustments regarding dose appropriateness…”
Section: Resultsmentioning
confidence: 99%
“…Yao et al reported that underdosing was associated with a higher risk of stroke particularly in apixaban‐treated patients, where the difference was statistically significant (HR: 4.87; 95% CI: 1.30 to 18.26; P = .02). 11 In dabigatran‐ or rivaroxaban‐treated patients without a renal indication there was no statistically significant difference . Furthermore, studies suggested that off‐label underdosing of apixaban without following the dose‐reduction criteria is associated with a nearly 5‐fold increased risk of stroke .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations